The Production of Metabolites by Saccharomyces Cerevisiae and its Application in Biotechnological Processes - Santos, Maria do Socorro Mascarenhas; Batistote, Margareth; Cardoso, Claudia Andrea Lima (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
Saccharomyces cerevisiae yeasts are widely known and used in biotechnological processes, as they have an excellent metabolic capacity that results in the formation of natural products with high added value. Thus, this study aims to present a view on the production of metabolites by Saccharomyces cerevisiae and their application in biotechnological processes. For this, a bibliometric analysis was carried out on the scientific production regarding the use of yeasts in biotechnological tests for the production of substances by activating their metabolic pathways. The articles found in the range between the years 2014 to 2019 are mostly research articles 57% and the rest 43% review. The analysis of the production of articles per year showed an oscillation for both research and review articles, and the countries with the highest publication rate are the United States and China. The data demonstrate a growing interest in secondary metabolic pathways of S. cerevisiae. These microorganisms can be used for the production of different metabolites that are of industrial interest, as they have a purity content that results in high commercial value.